Non-linear optical spontaneous photoluminescence emission enhancement effect in wide gap gallium nitride thin films - Niehus, Manfred (2005)
With two interfering pulses from the 4th harmonic of a Nd-YAG laser we burnt a periodic lattice structure into the surface of GaN thin films. The lattice period of this permanent grating could be controlled between less than one and several tens of microns. Above the decomposition threshold, nitrogen evades from the sample surface, and the residual metallic gallium accumulates in the form of tiny droplets at the surfaces. The patterned structure shows structural similarities with microcavities. The question arises if the residual metallic gallium may act as a partially reflecting mirror. To test this hypothesis, we studied the steady-state and transient photoluminescence through the modulation of light emerging from the ubiquitous broad “yellow” photoluminescence band. The microlattice shows up by energy-equidistant spontaneous emission enhancement peaks in the steady-state photoluminescence spectra. We suggest that the partial reflection due to the residual metallic gallium leads to the observed enhancement effect.